2015
DOI: 10.1021/pr501266c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reevaluation of FASP and Enhanced FASP Methods by LC–MS/MS

Abstract: Filter-aided sample preparation is a proteomic technique for the preparation and on column proteolysis of proteins. Recently an enhanced FASP protocol was developed that uses deoxycholic acid (DCA) and that reportedly enhances trypsin proteolysis, resulting in increases cytosolic and membrane protein representation. FASP and eFASP were re-evaluated by ultra-high-performance liquid chromatography coupled to a quadrupole mass filter Orbitrap analyzer (Q Exactive). Although there was no difference in trypsin acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 27 publications
1
42
1
Order By: Relevance
“…Although we did not detect similar differences in the human system, Leon et al observed that the combination of detergents for FASP had a severely negative impact on peptide recovery, 34 which is contradictorily discussed in the literature for FASP. 55,56 Although the performance of all detergents was superior compared to that with chaotropic salts, in particular, on membrane proteins, we found that urea-and Gua-containing buffers showed a significant enrichment of a number of different proteins. Most apparent was the enrichment of ribosomal proteins in bacteria and human cells ( Figure 2G,H and Table S3, Supporting Information) when sample preparation was carried out in the presence of Gua.…”
Section: Different Sample Preparation Strategies Enriched Specific Prmentioning
confidence: 84%
“…Although we did not detect similar differences in the human system, Leon et al observed that the combination of detergents for FASP had a severely negative impact on peptide recovery, 34 which is contradictorily discussed in the literature for FASP. 55,56 Although the performance of all detergents was superior compared to that with chaotropic salts, in particular, on membrane proteins, we found that urea-and Gua-containing buffers showed a significant enrichment of a number of different proteins. Most apparent was the enrichment of ribosomal proteins in bacteria and human cells ( Figure 2G,H and Table S3, Supporting Information) when sample preparation was carried out in the presence of Gua.…”
Section: Different Sample Preparation Strategies Enriched Specific Prmentioning
confidence: 84%
“…FASP was designed for the removal of detergents (in particular SDS), chaotropes, and reducing agents that are commonly used for the extraction and solubilization of proteins, and for reduction of disulfide bonds prior to protein digestion [76]. In addition, FASP removes nonproteinaceous components such as salts, nucleic acids, and lipids.…”
Section: Filter-aided Sample Preparation (Fasp)mentioning
confidence: 99%
“…The addition of DOC significantly increased the efficiency of trypsin digestion for both cytosolic and membrane proteins. FASP and eFASP have been compared in terms of the number of identified proteins and protein coverage in a shotgun proteomic experiment [76]. The results indicated that FASP and eFASP showed no significant differences at the protein identification level.…”
Section: Filter-aided Sample Preparation (Fasp)mentioning
confidence: 99%
“…Nowadays, new methods of dissociating in gas-phase peptides/proteins ions during MS/MS, such as electron-capture dissociation and electron-transfer dissociation in addition to collision-induced dissociation, are specially used in proteomic studies to characterize post-translational modifications [62]. A new method for sample preparation that bypasses many of the challenges associated with traditional protein purification protocols, improving sensitivity, recovery and proteomic coverage is the filter-aided sample preparation [63]. Proteins can be extracted using detergents or solubilizing agents (sodium dodecyl sulfate or 8M urea) and then subjected to sequential buffer exchange steps in spin filter units to fully remove unwanted compounds.…”
Section: Technological Proteomics Improvementsmentioning
confidence: 99%